Money : myths, truths and alternatives - Mellor, Mary (Policy Press, 2019)
Mary Mellor examines money's social, political and commercial histories to debunk longstanding myths such as money being in short supply and needing to come from somewhere. She sets out a new finance system, based on green and feminist concerns, to bring radical change for social good.